The Oxidative Response of Human Monocytes to Surface Modified Commercially Pure Titanium - De Poi, Robert P.; Kowolik, Michael; Oshida, Yoshiki; El Kholy, Karim (Frontiers in Immunology, 2021)
Cellular responses to implanted biomaterials are key to understanding osseointegration. The aim of this investigation was to determine the in vitro priming and activation of the respiratory burst activity of monocytes in response to surface-modified titanium. Human peripheral blood monocytes of healthy blood donors were separated, then incubated with surface-modified grade 2 commercially pure titanium (CPT) disks with a range of known surface energies and surface roughness for 30- or 60-min. Secondary stimulation by phorbol 12-myrisate 13-acetate (PMA) following the priming phase, and luminol-enhanced-chemiluminescence (LCL) was used to monitor oxygen-dependent activity. Comparison among groups was made by incubation time using one-way ANOVA. One sample from each group for each phase of the experiment was viewed under scanning electron microscopy (SEM) and qualitative comparisons made. The results indicate that titanium is capable of priming peripheral blood monocytes following 60-min incubation. In contrast, 30 min incubation time lead to reduced LCL on secondary stimulation as compared to cells alone. At both time intervals, the disk with the lowest surface energy produced significantly less LCL compared to other samples. SEM examination revealed differences in surface morphology at different time points but not between differently surface-modified disks. These results are consistent with the hypothesis that the titanium surface characteristics influenced the monocyte activity, which may be important in regulating the healing response to these materials.